Novel Cellulosic Fiber Composites with Integrated Multi-Band Electromagnetic Interference Shielding and Energy Storage Functionalities - Han, Xuewen; Hao, Cheng; Peng, Yukang; Yu, Han; Zhang, Tao; Zhang, Haonan; Chen, Kaiwen; Chen, Heyu; Wang, Zhenxing; Yan, Ning; Pu, Junwen (Nano-Micro Letters, 2025)
In an era where technological advancement and sustainability converge, developing renewable materials with multifunctional integration is increasingly in demand. This study filled a crucial gap by integrating energy storage, multi-band electromagnetic interference (EMI) shielding, and structural design into bio-based materials. Specifically, conductive polymer layers were formed within the 2,2,6,6-tetramethylpiperidine-1-oxide (TEMPO)-oxidized cellulose fiber skeleton, where a mild TEMPO-mediated oxidation system was applied to endow it with abundant macropores that could be utilized as active sites (specific surface area of 105.6 m2 g−1). Benefiting from the special hierarchical porous structure of the material, the constructed cellulose fiber-derived composites can realize high areal-specific capacitance of 12.44 F cm−2 at 5 mA cm−2 and areal energy density of 3.99 mWh cm−2 (2005 mW cm−2) with an excellent stability of maintaining 90.23% after 10,000 cycles at 50 mA cm−2. Meanwhile, the composites showed a high electrical conductivity of 877.19 S m−1 and excellent EMI efficiency (> 99.99%) in multiple wavelength bands. The composite material’s EMI values exceed 100 dB across the L, S, C, and X bands, effectively shielding electromagnetic waves in daily life. The proposed strategy paves the way for utilizing bio-based materials in applications like energy storage and EMI shielding, contributing to a more sustainable future. Highlights: 1 A mild 2,2,6,6-tetramethylpiperidine-1-oxide mediated modification system was applied to improve the reactivity and introduce porous structure of cellulose fiber skeleton. 2 Composite exhibited highly efficient electromagnetic shielding interference performance (> 99.99%) over multi-band. 3 Integrating energy storage, electromagnetic interference shielding, and structural design into bio-based materials.